Predictors of entrepreneurial intention among youths in Malaysia - Abu Samah, Bahaman; Omar, Siti Zobidah; Bolong, Jusang; Hassan, Md. Salleh (Universiti Putra Malaysia Press, 2018)
This study aims to examine the factors affecting entrepreneurial intention among youths in Malaysia. This study is quantitative in nature, and made use of a questionnaire as the main data-collection tool. Via multi-stage cluster sampling, a total of 400 youths from four districts in Peninsular Malaysia were selected as respondents. The analysis confirmed that all of the factors studied were found to have positive and significant relationship with entrepreneurial intention. Further analysis concluded three factors, namely attitude towards entrepreneurship, entrepreneurship knowledge and perceived feasibility, are the most significant factors contributing towards entrepreneurial intention among youth. These three factors (attitude towards entrepreneurship, entrepreneurship knowledge and perceived feasibility) need to be given particular emphasis in order to promote entrepreneurship intention among the target group. In other words, if these three factors among the target group were to be strengthened, there would be a greater likelihood that the group's entrepreneurship intention would be increased.